(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article analyzes anthropometric and functional indicators of 300 school-age children aged 8-14 living in Urgench. The study studied parameters such as height, body weight, body mass index (BMI), chest circumference, vital lung volume (VLV), arm muscle strength (dynamometry), arterial pressure and heart rate depending on age and gender. The results showed that age-related progressive changes were observed in the physical development of children, as well as the presence of gender differences in some indicators.